The Effect Of Corporate Governance And Risk Management On Banking Performance In Indonesia (Case Study Of Private Banks, State-Owned Banks And Regional Development Banks That Have Gone Public On The Indonesia Stock Exchange) - Samsaga, Fika Angry; Nelly, Apri Yeni; Giriati, Giriati; Wendy, Wendy (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This quantitative research aims to analyse the effect of corporate governance and risk management on banking performance in Indonesia. There are six predictors used to explain banking financial performance (GCG, NPL, NIM, LDR, BOPO and CAR). Sample selection resulted in 240 issuers during 2016-2023 with a total of 30 observations. Data analysis uses panel data regression by first selecting a research model. This research also controls two variables (SIZE and AGE) that are thought to affect the financial performance of banks. The results show that this model shows that the two main variables that significantly affect ROA are NIM and BOPO. NIM has a positive effect, indicating that an increase in net interest income will increase bank profitability. In contrast, BOPO has a negative effect, indicating that operational efficiency is very important in improving the financial performance of banks. Meanwhile, other variables such as GCG, NPL, LDR, and CAR do not show a significant effect, although CAR is close to the significance level.